Safety and efficacy of intensified versus standard dosing regimens of enteric-coated mycophenolate sodium in de novo renal transplant patients - Sommerer, Claudia; Glander, Petra; Arns, Wolfgang; Ariatabar, Tofan; Kramer, Stefan; Vogel, Eva-Maria; Shipkova, Maria; Fischer, Wolfgang; Liefeldt, Lutz; Hackenberg, Ruth; Schmidt, Jan; Zeier, Martin; et al. (Transplantation, 2011)
Background: Efficacy and safety of an intensified dosing (ID) regimen of enteric-coated mycophenolate sodium (EC-MPS), which achieves higher mycophenolic acid exposure early posttransplantation, were evaluated in comparison with a standard dosing (SD) regimen. Methods: In total, 128 de novo kidney transplant recipients treated with basiliximab induction, cyclosporine A, and steroids were randomized (1:1) to receive EC-MPS as SD (1440 mg/day; n=65) or ID (days 0–14: 2880 mg/day; days 15–42: 2160 mg/day; followed by 1440 mg/day; n=63). Efficacy parameters, safety, and tolerability were assessed over a 6-month study period. The primary endpoint was mean time to first occurrence of treatment failure. Results: Mean time to treatment failure was 130 days (95% confidence interval [CI]: 81–n/a) in the ID group versus 114 days (95% CI: 15–155) in the SD group (P=0.36). Similar percentages (ID 30.2%; SD 36.9%) experienced treatment failure. Biopsy-proven acute rejection occurred in 2 (3.2%) ID versus 11 (16.9%) SD patients (P<0.001). Three (2.3%) deaths (2 SD, 1 ID) and five (3.9%) graft losses (3 SD, 2 ID) occurred. Renal function, incidence of infection, and hematologic disorders were comparable in both study cohorts. Gastrointestinal disorders occurred in 51 (81.0%) ID and 49 (75.4%) SD patients with overall similar tolerability as assessed by the Gastrointestinal Symptom Rating Scale. Conclusion: In this exploratory study, the EC-MPS ID regimen reduced the incidence of rejection and showed a comparable safety and tolerability profile to SD. Further examination of this approach in a larger patient cohort is now warranted to confirm these findings.
Gesehen am 19.10.2022